A Typology of Family Relationships among Older Adults in Prison - Avieli, Hila (The prison journal, 2024)
Despite the growing interest in older incarcerated persons, the issue of their relationships with their families has been understudied. Therefore, the aim of the present study was to explore the ways in which older adults in prison construct, maintain, and navigate familial relationships with spouses and/or adult children. Interpretive phenomenological analysis was utilized to analyze interviews with 33 incarcerated older adults. Three themes emerged: (1) Keeping in touch; (2) cutting-off, and (3) forming an alternative family. Socioemotional selectivity theory is used to discuss the findings, suggesting that most participants wished to keep in contact with their families.